(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Pregnancy and its outcome of childbirth is a completely physiological process that is normal labour , during this journey there might some complication in that case Lower Segment Caesarean Section (LSCS) is a major obstetrics operation for saving the life of the women and newborns from birth related complication. Now a days rising trends of caesareansection are a major public health concern of potential maternal and perinatal risk. According to Robson 10 group classification try to evaluate the reasons of rising rates. This evaluation system were adopted Robson classification as the official name ‘Robson TGCS’ which was approved by WHO in October 2014. The Robson classification system classifies all women of deliveries into ten group based on a set of predefined obstetric parameters. In RTGCS 1-includes Nulliparous women with a single cephalic pregnancy ³37 weeks gestation in spontaneous labour. 1 Among this group some of the patients developed some complication and need caesarean section .In our country once the patient had an caesarean section then her subsequent pregnancies will delivered by LSCS. So, this study was designed of Robson TGCS 1 patient, to see the clinical profile, indication of primary LSCS between public versus private hospital in this city. Materials and methods: A prospective observational study was designed between Chittagong Medical College Hospital (CMCH) and Surgiscope Hospital Private Limited (SHL) 50 patients of RTGCS 1 from each of the hospital from May 2022-October 2022. Results: In CMCH – patients admitted into labour pain with complication 37(74%), but in SHL it is 7(14%). In CMCH 13(26%) admitted without complications whereas in SHL 34(86%).In CMCH - normal vaginal delivery + instrumental deliveries were 17(34%), and in SHL it is 36(72%). Rate of caesarean section in CMCH 33(66%) but SHL 14(28%). The most commonest indication of caesarean section due tofetal distress in CMCH 11((22%), in SHL 7(14%). In SHL there are 4(8%) were CDMR (Caesarean delivery for maternal request) but none of the patients with CDMR were in CMCH underwent caesarean section. Conclusion: Our main objective is to reduce the rate of primary LSCS among RTGCS 1. Every intervention have some complication. so, we have to ensure appropriate care during antenatal care and intranatal monitoring thus can reduce the rate of primary caesarean section. JCMCTA 2023 ; 34 (2) : 36-41